Problema de cobertura por vértices em redes complexas - Silva, Mariana Oliveira da (2013)
Graph theory is a mathematical tool used in solving many algorithmic and computational problems in that both sets of model elements and relationships between these elements. Most natural and technological systems can be mathematically modeled by graph having many well known properties, in particular the power law distribution of the vertex degree sequence. Examples of such graphs, called power law graphs are the Internet, World-Wide Web, social networks, biological networks. In the context of algorithmic problems on graphs, we are interested in problems in class NP-Hard, more speciﬁcally in the vertex cover problem. This work will be studied experimentally the behavior of an algorithm based on a greedy strategy for the vertex cover problem and compare with other approximation algorithms and with the exponential optimal solution. In particular this solution will be applied and analyzed in complex networks.